ASSESSMENT OF EXPLOSIVE STRENGTH IN SHOTOKAN PRACTITIONERS AT CSU MEDICINE TÂRGU MUREȘ - Cristian Graur; Norbert Steff; Rareș Alexandru Puni; Eniko Gabriella Papp; Laura Edit Ciulea (Sport şi Societate)
Shotokan is a style of karate, is a light contact style based on the speed, emphasizes technique, and accuracy.The testing was conducted on a group of10 athletes, category U16, of the Shotokan karate style, using the Optojump device. The test executed with the Optojump device was the 60-second jump test following the standard execution protocol for this test. The aim was to monitor the average height reached by the center of gravity during the execution of the test, the ground contact time, and the flight time.Following the implementation of a program created with the help of the TRX system, significant changes occur in the level of explosive strength in the lower body.